(untitled) (Tempo e Argumento, 2010)
This paper studies a homoerotic sociability network in Rio de Janeiro in the decade of 1960 through an analysis of reports contained in the journal "O Snob" (1963-1969) produced by a group that formed this network and that circulated among its participants. This is an investigation of identity constructions that those characters held in a sociability area segregated by the larger society but, at the same time, in dialogue with it. Analyzing issues commented internally by these groups with the backdrop of the prevailing norms of heterocentric behavior in the period, I identified the existence of original experiments in search of a "normal homosexual body". Sociosexual changes promoted by these experiments reflected in their sociability spaces and in sexual partnerships, facilitating the emergence of new sexual and/or emotional possibilities. So, I try to demonstrate that the form of integration undertaken by the study groups was directly linked to an inflexibility of gender roles of the time, and, over time, it started to detach from this rigidity in order to built new ways of acting. The study of the peculiar trajectory of groups that formed the network, linking it to the identity movements of the time, can contribute to discussions of individual rights history, specifically the struggle for sexual equality, and the debate over gay occupying spaces.